Social loafing and loan repayment accountability in group-based microbusiness financing / Farah Aida Ahmad Nadzri, Normah Omar and Rashidah Abdul Rahman - Ahmad Nadzri, Farah Aida; Omar, Normah; Abdul Rahman, Rashidah (Universiti Teknologi MARA Cawangan Selangor, 2017)
Although individual lending is not unusual in microfinance, group lending, however, is considered as more common in this field. Through group lending, all group members are made responsible for the repayment of their loans. The group-based model financing is also viewed as effective in transferring the risk from the providers to the borrowers by imposing the social cost on the borrowers. Despite the high repayment rate recorded by the group-based microfinance institutions, there are arguments that this method of financing may lead to "social loafing", a concept related to a reduction of an individual's effort when working in a group. As there is limited research in this area, this study aims to explore the existence of such scenario in the largest and oldest microfinance institution in Malaysia, Amanah Ikhtiar Malaysia. Based on the observation and interviews with the members of the organization, this study found that to some extent "social loafing" does exist in Amanah Ikhtiar Malaysia. Although the situation is not common, "social loafing" is a serious issue that needs to be controlled in the organization as it is believed that it is contagious and may affect the whole organization in a long run.